The Role of the Compost House in Overcoming Waste Problems in the Traditional Village of Padangtegal, Ubud - Setiawan, I Putu Heri; Wirawibawa, Ida Bagus Gde (Universitas Ibn Khaldun Bogor, 2023)
Garbage is one of the problems faced by almost every region in Indonesia. Padangtegal Traditional Village, Ubud is no exception. The existence of waste in the Padangtegal Traditional Village is one that gets more attention from village officials, where the Padangtegal Traditional Village makes policies that can help overcome its waste problems. Apart from the village apparatus, the provincial government also provided support for the Padangtegal Traditional Village in overcoming the waste problem. This is proven by the existence of a TPST located in the Padangtegal Traditional Village or what is often called the Compost House by the community. In assessing the role of the compost house, interviews were conducted with village officials and several members of the community. Where the results of this study are expected to help optimize waste management and overcome waste problems so that the environment becomes cleaner.